Progress in Propulsion Physics 2011
DOI: 10.1051/eucass/201102081
|View full text |Cite
|
Sign up to set email alerts
|

Agglomeration in solid rocket propellants: novel experimental and modeling methods

Abstract: Metal agglomeration is a key factor a¨ecting the performance of metalized solid propellant rockets since many of the mechanisms that degrade speci¦c impulse can be ascribed to metal powder aggregation and agglomeration. Condensed combustion products are generated at or near the burning surface of the propellant and then released in the gas phase where they are shaped by the core §ow viscous forces and oxidized by the reactive environment. On this basis, detailed information about the size of agglomerates as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The hazardous properties of the propellant compositions to impact stimuli were determined by applying the fall hammer method (2 kg drop weight) in a Bruceton staircase apparatus [16] and results were given in terms of the statically obtained 50 % probability of explosion (H 50 ). The friction sensitivity was measured with a Julius Peter apparatus [17] by incrementally increasing the load from 0.2 to 36 kg, until no ignition was noted in five consecutive test samples.…”
Section: Hazardous Properties Testmentioning
confidence: 99%
“…The hazardous properties of the propellant compositions to impact stimuli were determined by applying the fall hammer method (2 kg drop weight) in a Bruceton staircase apparatus [16] and results were given in terms of the statically obtained 50 % probability of explosion (H 50 ). The friction sensitivity was measured with a Julius Peter apparatus [17] by incrementally increasing the load from 0.2 to 36 kg, until no ignition was noted in five consecutive test samples.…”
Section: Hazardous Properties Testmentioning
confidence: 99%
“…In previous papers, the authors showed that an agglomeration process could be correlated to the pocket size through higher-order statistical descriptors [11,18,30]. The radial distribution function (RDF; also known as pair-correlation function) belongs to the family of second-order statistics.…”
Section: A Dimension Of Pocketmentioning
confidence: 99%
“…Some hundreds of agglomerates were measured after the release from the combustion surface by means of a consolidated optical technique based on high-speed camera visualizations and long-range microscopy [11]. The current experimental procedure enables measurements of items as small as 30 μm, for combustion occurring in the range of 5 to 40 bar.…”
Section: Potential Agglomeration: Experimental Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their characteristic time was defined as t ch = 2l ch / ṙ and was found to follow the relation D 43 = 2.892 t ch 0.997 , where D 43 is the average agglomerate diameter taken from experiments, and ṙ is the propellant burning rate. In a later work, Maggi et al [24] combine a theoretical 2D and 3D numerical packing approach with careful analysis of experimental high-speed photography of propellant combustion. They show good agreement between model predictions and experimental results, and suggest a nearly-linear relation between propellant characteristic time, as defined by [23], and the ejected agglomerate diameter.…”
Section: Introductionmentioning
confidence: 99%